The sternal brush of the Van der Vecht organ scales isometrically with body size: implications for the study of incipient morphological castes in primitively eusocial wasps. Issue 5 (3rd September 2017) - de Souza, André R.; Baptista, Camila Folly; Lino-Neto, José
Abstract : Recent studies have revealed a slight degree of queen–worker morphological divergence in wasps with a primitively eusocial organization, even though, by definition, they lack physical castes. Previously, we showed that in the Neotropical paper wasp Polistes versicolor, the cuticular excretory area of the Van der Vecht organ is disproportionally bigger in queens than in workers (non-isometric difference). Here, we look for caste difference in another component of the same organ, the sternal brush – a tuft of hairs arising from the excretory area. We found that the number of hairs in the sternal brush is higher in queens than in workers. Contrary to our expectation, such a difference is the result of an isometric growth, as caste difference vanishes after correcting for the wasp's overall body size. For the reason that only non-isometric relations are considered evidence of queen–worker divergence, we state that there is no morphological caste difference regarding the sternal brush of the Van der Vecht organ. Thus, the number of hairs in the sternal brush and the excretory area from which these hairs emerge have different scaling relations with the wasp's body size (isometric and non-isometric, respectively). We discuss implications for the study of incipient morphological castes in primitively eusocial wasps.